Perkembangan Pendidikan Islam di Indonesia pada Masa Klasik dan Modern - Febriansyah, Muhammad Raihan; Andriyani; Lusida, Nurmalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Understanding the history and dynamics of Islamic education and making effective policies in the future are necessary for the advancement of Islamic education in Indonesia, from classical to modern times. Pesantren became the centre of religious learning and knowledge in the past, shaping Indonesia's religious and cultural identity. The transformation of Islamic education experiences challenges such as limited access and quality of education issues and is influenced by modernisation, globalisation and technological advances today. This research uses the literature method and a qualitative approach by collecting data from various sources, such as books, journals and digital sources. This allows for a more in-depth understanding of the historical development and tracking of progress. Islamic education is constantly evolving to meet the needs of the times while maintaining the core values of Islam. To improve Islamic education, it requires strengthening educational institutions, improving teachers' capacity, developing relevant curricula, co-operation between institutions, government, and society, and greater public participation.